ANALYSIS OF GRDP BY BUSINESS FIELDS THAT INFLUENCE THE RATE OF ECONOMIC GROWTH IN BLORA DISTRICT IN 2023 - Yudhistira Adisputra, R.; Adianita, Happy; Susilowati, Dados; Dedi Marahendra, Wawan (Universitas Islam Lamongan, 2024)
This research aims to analyze GRDP according to Business Fields which influence the economic growth rate of Blora Regency. This research uses secondary and primary data. This research uses secondary data, namely Gross Regional Domestic Product (GRDP) According to Business Fields Based on Constant Prices for the 2013-2022 Base Year, GRDP. Secondary data comes from BPS (Central Statistics Agency), while primary data comes from Blora Regency Bappeda employees. Data was obtained using the documentation method. The data was processed using the Pearson Correlation Analysis technique using SPSS 20 to determine the strength or weakness of the relationship between the 17 business sector variables (X) and the GRDP variable (Y) of Blora Regency. Based on the results of the Correlation analysis, there are five sectors that are the base sectors in Blora Regency, the Financial Services and Insurance sector, the Government Administration, Defense and Social Security sectors, Real Estate and Wholesale and Retail Trade and Education Services. The Financial Services and Insurance sector has the largest level of closeness or correlation of 97.18% with a time span of 10 years.